Seismic assessment of the multi storey structural building model in accordance with euro code 8 and new Malaysian annex guidelines - Syed Muhammad, Bilal Haider (2019)
Multiple Earthquakes that occur during short seismic intervals affect the inelastic behavior of the structures. Sequential ground motions against the single earthquake event cause the building structure to face loss in stiffness and its strength. Although, numerous research studies had been conducted in this research area but still significant limitations exist such as use of traditional design procedure which usually considers single seismic excitation; and selecting a seismic excitation data based on earthquake events occurred at another place and time. Therefore, it is important to study the effects of successive ground motions on the framed structures. The objective of this study is to overcome the aforementioned limitations through testing a two storey reinforced concrete (RC) building structural model scaled down to 1/10 ratio through a similitude technique Buckingham Pi theorem. The scaled model is examined using a shaking table. Thereafter, the experimental model results are validated with simulated results using ETABS software. The test framed specimen is subjected to sequential five artificial and four real-time earthquake motions. Dynamic response history analysis has been conducted to investigate the observed response and crack pattern; maximum displacement; residual displacement; residual interstorey drift ratio, serviceability limit state, ultimate limit state, acceleration response, interstorey drift ratio and storey drift ratio. The results of the study concluded that the framed model highlighted the structural strength against its ductility, which is justified through the model ability to resist the multiple ground motions in low seismicity region (i.e. Malaysia) under extreme PGAs’ up to 0.82g. Displacement parameters showed that real-time successive ground motions had not severely affected the RC model, as the maximum PGA in sequential motion was 0.34g. However, artificially produced seismic motions show that the intense PGAs (i.e. 0.25g to 0.82g) cause the framed structure to displace each storey twice in correlation with vary first artificial seismic vibration. Therefore, traditional seismic design Euro code 8 (EC8) is required to reconsider the traditional design procedure and damage limitation criteria for multiple ground motions.